ECONOMIC ANALYSIS OF POWER PLANT USING UNIT COMMITMENT SCHEDULING - Ratih Puspita Siwi; Ayu Annisa Akbar; Lista Litta; Andi Alviadi Nur Risal (Jurnal Media Elektrik, 2024)
Unit commitment is the scheduling of disconnected generation of generating units in an electric power system within a certain period, with the aim of meeting load demand. This scheduling is usually determined based on human load demand which always changes over time. This research aims to determine the production costs of thermal plants using the Second Order Gradient method to obtain economical operating costs, to determine fuel costs based on plant loading, and to determine the most economical scheduling using unit commitment. This is to determine the most optimal on/off schedule for generating units to be operated to meet the estimated load to achieve minimum fuel costs in rupiah.